Training, Trust, and Technology: A Mixed-Methods Study of Latin American Extension Workers’ Experiences During COVID-19 - Pablo Lamiño Jaramillo; Amy Boren-Alpizar; Sarahi Morales Vanegas; Carla Millares-Forno (Journal of International Agricultural and Extension Education, 2022)
The COVID-19 pandemic has drastically affected people's lives around the world, including agricultural extension workers. To date, few studies have been conducted to understand the adaptation of extension services in Latin American countries during the pandemic. This mixed-methods study explored Latin-American extension professionals’ preparation to implement knowledge-sharing activities and sought to understand extension professionals' responsiveness to COVID-19. The results revealed significant differences in extension responsiveness, between field extension workers and in-office extension workers. Delving into this difference revealed that field extension professionals perceived lower responsiveness because they were not able to continue their pre-pandemic, face-to-face activities in the field with farmers; on the other hand, office extension workers were able to complete and respond to their annual program objectives by increasing institutional partnerships by virtual means. Resilience was found in the two phases of this study. Extension professionals were viewed by farmers as a reliable resource for addressing COVID-19 challenges. Extension professionals began using new communications technologies to train farmers, even though they were not trained in these technologies themselves. It will be important to begin formally incorporating the use of new technology, and alternative communication strategies with communities during crises, as part of preparation for field technicians.
Keywords: extension; Latin America; COVID-19; resilience; mixed-methods